The modeling of the structurefoundation-base system with the use of two-layer beamon an elastic basis with variable coeficcient of subgrade reaction Моделирование системы здание — фундамент — основание двухслойной балкой на упругом основании с переменным коэффициентом постели - Barmenkova Elena Vjacheslavovna (Vestnik MGSU, 2013)
In the paper the author presents the results of calculations of the system «structurefoundation-base» in case of using the two-layer and the single-layer beam models on an elastic basis with variable and constant coefficients of subgrade reaction. The analytical solution is obtained using the method of initial parameters. The calculations are carried out in case of building up the structure.The method of calculating two-layer beam with variable flexural rigidity along the length on an elastic foundation was described in the author’s previous articles, while in the present paper variable coefficients of subgrade reaction are taken into account. A two-layer beam is a beam of variable rigidity, the lower layer simulates the foundation, and the upper — the structure, at the same time the weight of each layer is considered.For comparison, the problem is also considered in its traditional statement. That means the problem of single-layer beam bending is solved with cross-section of constant length, which is freely lying on an elastic basis of Winkler’s type.The results of calculations of two-layer and single-layer beams show, that the values of the internal forces and stresses are higher with variable coefficient of subgrade reaction than with the constant one. When comparing the two-layer and the single-layer beam models with the same foundation characteristics, the values of internal forces in two-layer beams are much higher.On the basis of the calculations we can make the following conclusion: in order to obtain more reliable prognosis of the stress-strain state of the system «structure-foundation» on an elastic basis, it is appropriate to carry out calculations with the use of a contact model in the form of a two-layer beam on an elastic basis of Winkler’s type with variable coefficients of subgrade reaction. The model allows us to take account of such factors as rigidity changes in the base and the rigidity of the upper structure. Приведены результаты расчетов системы здание — фундамент — основание с использованием моделей двухслойной и однослойной балок на упругом основании с постоянным и переменным коэффициентами постели. Двухслойная балка является балкой переменной по длине жесткости, нижний слой которой моделирует фундамент, а верхний — надфундаментную конструкцию, при этом учитывается собственный вес каждого слоя. Расчеты приведены с учетом наращивания надфундаментной конструкции.